2016
DOI: 10.3389/fncir.2016.00098
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Spectroscopic Glutamatergic Correlates of Cortical Excitability in Depressed Adolescents

Abstract: Introduction: Transcranial magnetic stimulation (TMS) research has suggested dysfunction in cortical glutamatergic systems in adolescent depression, while proton magnetic resonance spectroscopy (1H-MRS) studies have demonstrated deficits in concentrations of glutamatergic metabolites in depressed individuals in several cortical regions, including the anterior cingulate cortex (ACC). However, few studies have combined TMS and MRS methods to examine relationships between glutamatergic neurochemistry and excitato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Spectroscopy studies of neurotransmitter levels in ASD remain nuanced and conflicting at times 49 . Thus far, there is emerging evidence that ICF is positively associated with [1 H] MRS measures of glutamate 50,51 . Dyke et al studied the association of ICF with Glu/tCr levels in a 7 T [1 H] MRS. ICF demonstrated “substantial evidence” for a positive linear relationship with Glu/Cr levels using Bayesian classification (and a trend level Pearson’s correlation following Bonferroni correction (r = 0.52, p = 0.08 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spectroscopy studies of neurotransmitter levels in ASD remain nuanced and conflicting at times 49 . Thus far, there is emerging evidence that ICF is positively associated with [1 H] MRS measures of glutamate 50,51 . Dyke et al studied the association of ICF with Glu/tCr levels in a 7 T [1 H] MRS. ICF demonstrated “substantial evidence” for a positive linear relationship with Glu/Cr levels using Bayesian classification (and a trend level Pearson’s correlation following Bonferroni correction (r = 0.52, p = 0.08 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…69 Concurrent measures with TMS neurophysiological paradigms and 7 T MRS would provide a refined understanding of GABAergic and glutamatergic tone in disorders of the negative valence systems and mechanistic studies of brain stimulation treatments such as TMS. 69,70…”
Section: Future Directionsmentioning
confidence: 99%
“…In disease, a study by Pogarell et al ( 2006 ) revealed adaptions in the dopaminergic system in MDD patients following repetitive TMS (rTMS) treatment. Furthermore, an investigation by Lewis et al ( 2016 ) reported changes in cortical excitability in patients suffering from MDD in the primary motor cortex and the ACC (Lewis et al, 2016 ). Dubin et al ( 2016 ) were one of the first to investigate the therapeutic effect of TMS on neurotransmitter distribution using MRS, showing elevated GABA levels.…”
Section: Introductionmentioning
confidence: 99%